Developing a transformation readiness index for Industry 4.0: a case study of food logistics in the rice commodity sector - Ichsani, Firna Nur; Hasbullah, Hasbullah (Operations Excellence: Journal of Applied Industrial Engineering, 2024)
In 2021, it was recorded that Indonesia had a population of 272,682.50 million people, which then underwent an increase of 1.12% from the previous year to 275,773.80 million people in 2022. The rapid growth of the population will affect the food supply in Indonesia. It is known that many provinces in Indonesia still have a percentage deficit in food distribution, especially in the rice commodity, which needs to be improved to meet projected annual needs. This research tries to develop a transformation index by combining the Industry 4.0 concept model with the logistics operating in the food sector. To improve food security in Indonesia by transforming towards Industry 4.0. Research with a qualitative descriptive approach produces several factors that can influence the transformation index of food logistics companies in Indonesia towards Industry 4.0. The results of the use of technology, especially in encouraging transparent and real-time data transfer (horizontal and vertical) and decision-making in the logistics sector, are critical to pay attention to. However, organizational management, culture, and human resources are also essential things to pay attention to in transformation.